Sensitivity analysis of concave capacitance sensors for holdup measurement in two-phase flow - Huat, B.Y. (Asian Research Publishing Network, 2016)
Due to the complex flow structures of two-phase flow, the holdup measurement is a very challenging problem. In this paper, we use the finite element method to analyse a three-dimensional model of concave capacitance sensor. Both two-plate and four-plate sensors are investigated and compared in terms of the average sensitivity and sensitivity variation parameters. The average sensitivity of sensors is greatly increased during the shift from two-plate design to four-plate design. However, this causes the sensitivity variation parameter to be increased despite the usage of more plates. The geometry of the concave capacitance sensor is determined be 40° electrode angle for four-plate design has a better result as compared to 80° electrode angle of two-plate design. © 2006-2016 Asian Research Publishing Network (ARPN). All rights reserved.